2012
DOI: 10.2308/iace-50141
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring Tax and Audit Procedures: Implications for U.S.-Based Employee Education

Abstract: Large accounting firms are increasingly performing audit and tax work for U.S.-based clients (and clients of other highly developed countries) in offshore locations, particularly India. Such arrangements are advantageous because of the availability of a skilled labor pool at a substantially lower cost than U.S. personnel, and the ability of the firms to operate nearly around the clock due to time differences between the U.S. and India. However, offshoring also creates substantial challenges in managing engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Regarding monitoring as a component of internal control, periodic assessments of the effectiveness of internal controls by managers, internal auditors, and external auditors is one of the monitoring activities [14]. Studies by Wardiwiyono [7] found that monitoring in financing system should be implemented from the beginning to the end of process.…”
Section: Monitoringmentioning
confidence: 99%
“…Regarding monitoring as a component of internal control, periodic assessments of the effectiveness of internal controls by managers, internal auditors, and external auditors is one of the monitoring activities [14]. Studies by Wardiwiyono [7] found that monitoring in financing system should be implemented from the beginning to the end of process.…”
Section: Monitoringmentioning
confidence: 99%
“…Audit firms, like firms in many industries, now highly value college graduates with superior social skills—such as communication, teamwork, and leadership (Kuhn and Weinberger [], Deming []). Basic technical tasks, such as confirmations, that had been a priority of inexperienced auditors have been offshored (Daugherty, Dickins, and Fennema [], Hanes []). Offshoring enables inexperienced auditors to devote more time to assisting or performing socially complex tasks.…”
Section: Background On Tacit Knowledge and Hypothesis Developmentmentioning
confidence: 99%
“…Offshoring has become a common practice in the U.S. economy (Daugherty and Dickins 2009) and is expected to continue growing in the accounting profession, with key growth drivers being the need for efficient use of technology, the ability to work around the clock, the reduction of cost, and the utilization of talent across the world (Daugherty et al 2012). Audit firms use offshoring to delegate lower level audit tasks, such as accounts receivable confirmations, bank confirmations, and tying out of financial statements, to their offshore offices.…”
Section: Literature Review and Research Questions Development Use Of Offshoringmentioning
confidence: 99%
“…One such recent development is the use of outsourcing and/or offshoring in completing audit work. The growth of outsourcing and offshoring in accounting has influenced the types of learning experiences encountered by accounting professionals (Daugherty, Dickins, and Fennema 2012;Murphy 2014). Specifically, audit firms are pushing for lower level tasks to be performed by firm members outside the core audit team (PwC 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation